Improving Work Productivity of Medical Record Storage Officers in the Implementation of Medical Record Retention - Savitri Citra Budi; Budiana Marini (Universitas Muhammadiyah Yogyakarta, 2022)
Management of medical record storage area requires efforts to provide fast, precise, and accurate services. Shelf capacity in storage areas needs to be reviewed periodically. Sorting medical records that have met the shelf life into separate storage rooms is one of the effort that can be done. This article aims to examine medical record retention in Ajibarang Hospital and to explore some efforts to improve work productivity of medical record storage officers related to retention activity. This study was conducted using qualitative research method with an exploratory approach. The respondents were medical records storage officers at Ajibarang Hospital. Data were collected through in-depth interviews, documentation studies, and observation, then analyzed using atlas.ti 8 application, and validated using triangulation method. First medical record retention was carried out in 2017. After that, it was decided that the retention became a daily additional task for medical record storage officers. Through this study, some efforts are suggested to increase the work productivity of medical records storage officers such as providing equipment and materials, improving human resource, implementing policies, and allowing proper budget. Those suggestions are important to increase effectiveness in the implementation of medical record retention.